STRENGTHENING STUDENTS' CHARACTER THROUGH INTERNALIZATION OF THE NATIONALISM VALUES IN CURRICULUM MANAGEMENT - Ulpah Maspupah (Prodi Manajemen Pendidikan Islam FITK UIN Sunan Kalijaga Yogyakarta, 2022)
Bustan Tsamrotul Qolbis Salim (BTQ) Syiddiqiyyah is a children's educational institution that includes the concept of Nationalism in its education curriculum so that children from an early age have a love for the nation and culture of their country, namely Indonesia. This study aimed to describe the process of internalizing the values of the character of Nationalism in the BTQ Shiddiqiyyah Curriculum Management Practice, Ploso Branch, Jombang, East Java. The research method uses qualitative research with a qualitative descriptive approach. Data collection techniques using observation, interviews, and documentation. Data analysis techniques consist of data reduction, data presentation, and conclusion. The study results: The description of the process of internalizing the character values of loving the Motherland in the BTQ Shiddiqiyyah Curriculum Management Practice, Ploso Jombang Branch, East Java, is carried out through planning, organizing, implementing, and evaluating. Method of Internalizing Nationalism with